The marketing mix: a conceptual framework for teaching public relations and other corporate communication. (6th March 2015) - Komodromos, Marcos; Nicoli, Nicholas
This paper examines the concepts that are so often used interchangeably in the broad field of corporate communication. The authors first seek to define the field of marketing and how it has adapted to the fast pace of commerce and technology. In addition, the authors address one specific component of marketing in detail – that of advertising. This area of activity is no doubt the most conspicuous – and arguably – creative element of corporate communication. Because of this, advertising is often the one sector that becomes entangled in just how other areas of an organisation communicate. Indeed, there are cases where public relations professionals need to use the tools, tactics, know-how and accessibility of advertising in the same manner as advertisers often do when similar expertise is required from public relations (PR). Following, the study contributes to existing knowledge regarding the area of the marketing mix, which is used to communicate with customers within the public relations and corporate communications literature.